Comparative analysis of the treatment efficiency of the consequences of congenital transient hypothyroidism - Sharipova, Farida.K.; Sharipova, Feruza I. (International Journal of Psychosocial Rehabilitation, 2020)
Actuality: Taking into account the primary role of thyroid hormones in the formation and growth of the nervous system in children, the special importance of transient hypothyroidism among other endocrinopathies of newborns and children becomes evident, which makes it necessary to study it further.Methods: indications for treatment were: disorders of psychomotor and perceptual functions development, assessment of neuropsychiatric development below 21 points. 60 children were examined, patients were divided into 2 groups: Group 1 - 30 children received Piracitam treatment by the firm " Gedeon Reichter ". Patients of the 2nd group (30 children) were prescribed l-thyroxin as monotherapy. The results of treatment were monitored by changing clinical and psychological indicators with MDI scores. The examination was carried out at the beginning of treatment and 3 months after it.Results: there was a 1. 5 times decrease in hyperexcitability syndrome in the first group and 1. 8 times decrease in the second group and in vegeto-visceral dysfunction (9 times and 2 times respectively). Acceleration of mental development rates was noted almost 3 times in the first group and 1.3 times in the second group, as well as a reliable increase of CPR (21.2±1.3 and 25.6±1.4; P<0.05), while in the second group there was a noticeable increase of this index (20.1±0.9 and 22.8±1.1; P>0.05). It testifies to efficiency of application of complex therapy with prescription of Piracetam.Conclusion: the complex therapy with the use of the drug Piracetam for children with congenital transient hypothyroidism helps to timely correct identified mental disorders and can be recommended for the prevention of the mental consequences of CH.